Dose–response linearization in radiochromic film dosimetry based on multichannel normalized pixel value with an integrated spectral correction for scanner response variations. Issue 11 (26th September 2019) - Aldelaijan, Saad; Devic, Slobodan; Papaconstadopoulos, Pavlos; Bekerat, Hamed; Cormack, Robert A.; Seuntjens, Jan; Buzurovic, Ivan M.
Abstract : Purpose: To introduce a model that reproducibly linearizes the response from radiochromic film (RCF) dosimetry systems at extended dose range. To introduce a correction method, generated from the same scanned images, which corrects for scanner temporal response variation and scanner bed inhomogeneity. Methods: Six calibration curves were established for different lot numbers of EBT3 GAFCHROMIC™ film model based on four EPSON scanners [10000XL (2 units), 11000XL, 12000XL] at three different centers. These films were calibrated in terms of absorbed dose to water based on TG51 protocol or TRS398 with dose ranges up to 40 Gy. The film response was defined in terms of a proposed normalized pixel value ( n P V RGB ) as a summation of first‐order equations based on information from red, green, and blue channels. The fitting parameters of these equations are chosen in a way that makes the film response equal to dose at the time of calibration. An integrated set of correction factors (one per color channel) was also introduced. These factors account for the spatial and temporal changes in scanning states during calibration and measurements. The combination of n P V RGB and this "fingerprint" correction formed the basis of this new protocol and it was tested against net optical density ( n e t O D X = R, G, B ) single‐channel dosimetry in terms of accuracy, precision, scanner response variability, scanner bed inhomogeneity, noise, and long‐term stability. Results: Incorporating multichannel features (RGB) into the normalized pixel value produced linear response to absorbed dose (slope of 1) in all six RCF dosimetry systems considered in this study. The "fingerprint" correction factors of each of these six systems displayed unique patterns at the time of calibration. The application of n P V RGB to all of these six systems could achieve a level of accuracy of ± 2.0% in the dose range of interest within modeled uncertainty level of 2.0%–3.0% depending on the dose level. Consistent positioning of control and measurement film pieces and integrating the multichannel correction into the response function formalism mitigated possible scanner response variations of as much as ± 10% at lower doses and scanner bed inhomogeneity of ± 8% to the established level of uncertainty at the time of calibration. The system was also able to maintain the same level of accuracy after 3 and 6 months post calibration. Conclusions: Combining response linearity with the integrated correction for scanner response variation lead to a sustainable and practical RCF dosimetry system that mitigated systematic response shifts and it has the potential to reduce errors in reporting relative information from the film response.